Peningkatan Aktivitas Belajar Dan Kemampuan Membaca Teks Eksplanasi Melalui Model Inside Outside Circle Siswa Kelas VIII-F SMP Negeri 1 Mojoanyar - Inawati (Discovery : Jurnal Ilmu Pengetahuan, 2020)
Abstract: Reading ability of explanation text of grade VIII SMP students did not fulfill the MMC. The students were less enthusiastic in reading comprehension. Moreover, the learning method was still fetched up all standing in lecturing method. The students were passive, they just listened to what the teacher delivered. This fact encouraged teachers to develop the learning methods which stimulated students’ interest in reading explanation text. The researcher made serious effort to apply the Inside Outside Circle learning model. The aim was to improve learning activities and reading ability of explanation text. The object of this research was the eighth grade students of SMP Negeri 1 Mojoanyar Mojokerto. The method in this study used two cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. The research instrument used tests and non-tests. The results of the study in the Inside Outside Cicle model were: (1) the average level of learning activity was 60.00% (quite active category), to 86.88% (active category), an increase of 26.88%, (2) the average value -The class average of 72.53 becomes 77.69, an increase of 7.57%, (3) students whose grades are low, there is an increase in the value of 30.43%, (4) the number of students who achieve very good reading skills increases by 3.13%, ( 5) completeness of student learning increased 21.88%. From this, it can be seen that there is an increase in student learning activities from being less active in reading to being more active. Meanwhile, the increase in reading skills can be seen from the increase of test scores. Thus the application of the Inside Outside Circle learning model can improve learning activities and reading ability of Explanation text. Keywords : Learning activities,Reading ability of Explanation Text, Inside Outside Circle Learning Model Abstrak: Kemampuan membaca teks Eksplanasi siswa SMP kelas VIII belum memenuhi KKM. Siswa kurang bergairah dalam membaca pemahaman . Apalagi metode pembelajaran masih terpaku metode ceramah. Siswa bersikap pasif , hanya mendengarkan yang disampaikan guru. Kenyataan ini mendorong guru mengembangkan metode pembelajaran yang dapat merangsang siswa tertarik membaca Teks Eksplanasi. Penulis berupaya menerapkan model pembelajaran Inside Outside Circle. Tujuannya adalah untuk meningkatkan aktivitas belajar dan kemampuan membaca teks Eksplanasi. Objek penelitian ini adalah siswa kelas VIII SMP Negeri 1 Mojoanyar Mojokerto. Metode dalam penelitian ini menggunakan dua siklus, masing-masing siklus terdiri empat tahap yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi. Instrumen penelitian menggunakan tes dan nontes. Hasil penelitian pembelajaran model Inside Outside Cicle : (1) rata-rata tingkat aktivitas belajar sebesar 60,00% (kategori cukup aktif), menjadi 86,88% (kategori aktif), terjadi kenaikan 26,88%, (2) nilai rata-rata kelas 72,53 menjadi 77,69 naik 7,57% ,(3) siswa yang nilainya rendah , ada peningkatan nilai 30,43%,(4) jumlah siswa yang meraih kemampuan membaca amat baik meningkat 3,13% ,(5) ketuntasan belajar siswa meningkat sebesar 21,88%. Dari sini terlihat adanya peningkatan aktivitas belajar siswa dari yang kurang aktif membaca menjadi lebih aktif. Sedangkan dalam peningkatan kemampuan membaca terlihat dari meningkatnya nilai ulangan. Dengan demikian penerapan model pembelajaran Inside Outside Circle dapat meningkatkan aktivitas belajar dan kemampuan membaca teks Eksplanasi. Kata kunci : Aktivitas belajar, Kemampuan Membaca Teks Eksplanasi, Model Pembelajaran Inside Outside Circle.